Racial and Ethnic Disparities in Cancer-Associated Thrombosis - Wiredu, Courteney; Haynes, Norrisa; Guerra, Carmen; Ky, Bonnie (Thrombosis and Haemostasis, 2022)
Active malignancy increases the risk of developing venous thromboembolism (VTE) by four- to seven-fold. The risk of VTE, including deep vein thrombosis and pulmonary embolism, in patients with cancer varies based on several clinical factors, such as cancer stage and age. However, race and ethnicity are also associated with increased VTE risk. Black (African American) patients with cancer have a higher risk of developing VTE than White patients, while Asian/Pacific Islanders have a lower risk. Studies on cancer-associated thrombosis demonstrate a need to advance our understanding of both the biologic and sociologic underpinnings of the observed differences according to race. Addressing the causes of these disparities can better health outcomes for historically underserved patient populations.
Keywords: ethnic groups; neoplasms; race; risk factors; venous thromboembolism